Coaches` controlling interpersonal style and frustration of basic psychological needs in adolescent judokas - Pulido, S.; de la Vega, R.; Fuentes, J. P. (Journal of Human Sport & Exercise, 2022)
The aim of the study was to analyse the relationships established between the different factors that make up coaches` controlling interpersonal style and frustration of basic psychological needs, as well as to identify the differences that may exist in terms of gender and training hours, and whether the latter may trigger these variables in adolescent judokas. A socio-demographic questionnaire, the Controlling Coach Behaviors Scale (CCBS) (Bartholomew, Ntoumanis & Thøgersen-Ntoumani, 2010), in its Spanish version (Castillo et al., 2014), was administered, as well as the Psychological Need Thwarting Scale (PNTS) (Bartholomew, Ntoumanis, Ryan & Thøgersen-Ntoumani, 2011), also in its Spanish version (Sicilia, Ferriz & Sáenz-Álvarez, 2013). The sample comprised 86 adolescent judokas, who had a federation licence and participated in regional competitions (M = 14.13; SD = 1.38). Descriptive and correlation analyses of all variables were performed. The Mann-Whitney U-test and the Kruskal-Wallis test were carried out, respectively, to analyse the differences in gender and training hours. The results showed a positive and significant correlation between all study variables. In addition, significant differences were found between genders in the control variable of use of rewards, and in the frustration variable of the basic psychological need of competence, depending on the judokas` training hours. These results suggest that controlling interpersonal styles influence the frustration of basic psychological needs of adolescent judokas, according to their gender or training hours.